Effect of sepiolite addition on fibre-cement based on MgO-SiO₂ systems. (October 2019) - Mármol, Gonzalo; Savastano, Holmer; de la Fuente, Elena; Miranda, Rubén; Blanco, Ángeles; Negro, Carlos
Abstract: The addition of sepiolite in fibre-cement is analysed as a possible additive constituent of MgO-SiO2 binders. In order to optimise the Mg-SiO2 cementitious system in fibre-cement sheets, small cement replacement (1 and 2 wt%) by sepiolite is introduced and its effects are studied, firstly, in hardened cement pastes and, later, in fibre-cement systems. When used only in cement pastes, non-destructive studies are employed to assess flexural performance over time as well as the possible reactivity between additive and cement, proving that Elastic Modulus is increased. When sepiolite is introduced in fibre-cement, the properties of the slurry suspensions and its interference in the Hatschek process are studied. It is shown that sepiolite addition increases floc size of MgO-SiO2 systems. Finally, flexural tests are performed to understand the outcome of this additive of the mechanical performance of the samples, proving that sepiolite improves the product homogeneity, which is essential for industrial applications.